Librarians as information miners: the case of Nigeria (2014)
The need to resolve the question of what special skills librarians in Nigeria need to possess to enable them discover and harvest knowledge from digital libraries, know the retrieval engines and indexing structure as well as identify information needs, fine-tune and/or situate search terms in order to harvest results within the fastest speed/time possible cannot be over emphasized. This paper therefore evaluates the knowledge and skills needed by librarians in Nigeria to achieve optimum competence and performance in the digital environment. It examines the features of some internet databases with the aim of appropriating them to facilitate the digital consciousness of Librarians in the Nigerian digital environment, since these databases have similarities in structure; hence the aim is to facilitate high quality and timely research output. An acquisition of the relevant skills will facilitate librarians’ competence and performance in navigating, browsing and filtering digital reference services and electronic information services from the digital information sources. Relevant bodies or organizations that are directly responsible for the training and retraining of librarians are enjoined to organize among other activities, periodic workshops targeted at training librarians for the purpose of getting them ready for the challenges of the digital environment.